Data from: Multilocus analysis of nucleotide variation and speciation in three closely related Populus (Salicaceae) species - Du, Shuhui; Wang, Zhaoshan; Ingvarsson, Pär K.; Wang, Junhui; Wu, Zhiqiang; Tembrock, Luke R.; Zhang, Jianguo (2015)
Historical tectonism and climate oscillations can isolate and contract the geographical distributions of many plant species, and they are even known to trigger species divergence and ultimately speciation. Here, we estimated the nucleotide variation and speciation in three closely related Populus species, Populus tremuloides, P. tremula and P. davidiana, distributed in North America and Eurasia. We analysed the sequence variation in six single-copy nuclear loci and three chloroplast (cpDNA) fragments in 497 individuals sampled from 33 populations of these three species across their geographic distributions. These three Populus species harboured relatively high levels of nucleotide diversity and showed high levels of nucleotide differentiation. Phylogenetic analysis revealed that P. tremuloides diverged earlier than the other two species. The cpDNA haplotype network result clearly illustrated the dispersal route from North America to eastern Asia and then into Europe. Molecular dating results confirmed that the divergence of these three species coincided with the sundering of the Bering land bridge in the late Miocene and a rapid uplift of the Qinghai-Tibetan Plateau around the Miocene/Pliocene boundary. Vicariance-driven successful allopatric speciation resulting from historical tectonism and climate oscillations most likely played roles in the formation of the disjunct distributions and divergence of these three Populus species.